Structural characteristics and forage mass of Tifton 85 pastures managed under three post-grazing residual leaf areas - Silva, Wilton Ladeira da [UNESP]; Galzerano, Leandro [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Sociedade Brasileira de Zootecnia, 2013)
The experiment was carried out on Cynodon spp cv. Tifton 85 pastures grazed by sheep under rotational stocking, with the objective of evaluating the structural characteristics as well as the forage mass of the pastures subjected to three grazing intensities in successive cycles. Treatments were composed of three residual leaf area indices (rLAI; 2.4; 1.6 and 0.8), allocated in completely randomized blocks with seven replications, totaling 21 experimental units. Tiller population density, pasture height, leaf area index, forage morphological composition and pasture forage mass were evaluated. The rLAI modified the tiller population density, which increased linearly with decrease in the rLAI of the pastures. Dry masses of leaf blade, stem and dead material were inferior when the rLAI imposed were lower, which resulted in differentiated forage production among the treatments. Tifton 85 pastures grazed by sheep in rotational stocking under tropical conditions with different rLAI show a modified sward structure over successive grazing cycles, mainly by alteration in the height and LAI of the plants at pre-grazing and by light interception post-grazing, which change the tiller population density. The residual leaf area index of 1.6 is the most suitable for pasture management for being equivalent to the heights of entrance and exit of animals on and from paddocks of 33 and 19 cm, respectively, which avoid great accumulation of dead material and excessive stem elongation, in addition to ensuring tillering in the sward.
Keywords: Leaf area index; Light interception; Sheep; Rotational stocking; tillers